2015
DOI: 10.1002/pbc.25847
|View full text |Cite
|
Sign up to set email alerts
|

Orbital Metastasis Is Associated With Decreased Survival in Stage M Neuroblastoma

Abstract: Background Approximately 30% of patients with metastatic (stage M) neuroblastoma present with periorbital ecchymosis from orbital osseous disease. Though locoregional disease is staged by imaging, the prognostic significance of metastatic site in stage M disease is unknown. We hypothesize that, compared to non-orbital metastasis, orbital metastasis is associated with decreased survival in patients with stage M neuroblastoma, and that periorbital ecchymosis reflects location and extent of orbital disease. Pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…2 I – I ″ ), corresponding to the most prevalent sites of neuroblastoma metastases in humans. Of note, metastases in bone marrow, bony orbit, and lung are associated with poor prognosis and decreased survival in neuroblastoma patients ( 3 5 ). Tumor cells from both LIN28B_WT;MYCN and LIN28B_MU;MYCN lines were also identified in sites that are less commonly associated with human neuroblastoma metastasis, such as the pancreas ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 I – I ″ ), corresponding to the most prevalent sites of neuroblastoma metastases in humans. Of note, metastases in bone marrow, bony orbit, and lung are associated with poor prognosis and decreased survival in neuroblastoma patients ( 3 5 ). Tumor cells from both LIN28B_WT;MYCN and LIN28B_MU;MYCN lines were also identified in sites that are less commonly associated with human neuroblastoma metastasis, such as the pancreas ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Neuroblastoma derives from the sympathoadrenal lineage of neural crest cells and typically arises in the adrenal medulla or paraspinal ganglia ( 1 ). Over half of neuroblastomas exhibit metastases at diagnosis with frequent spread to bone marrow, cortical bone, lymph nodes, liver, brain, orbital sites, and lung ( 1 5 ). It is, therefore, critical to devise new strategies for the treatment of this high-risk pediatric malignancy.…”
mentioning
confidence: 99%
“…Based on the above findings, infiltration of local soft tissue through bone marrow and bone metastasis is believed to be a route of tumor cell metastasis to the head and facial soft tissue. Harreld [4] reported that 30% of children with NB older than 18 months with distant metastasis had periorbital bone and soft tissue metastasis; among them, children with manifestations of soft tissue metastasis such as periorbital bruising had a worse prognosis. Children with central nervous system and intracranial metastases of NB also had a poor prognosis, showing a high mortality rate.…”
Section: Discussionmentioning
confidence: 99%
“…These metastases are most frequently observed in the bone and bone marrow [2,3] , and periorbital soft tissue involvement is more common than in other non-periorbital tumors. Harreld [4] reported that 30% of pediatric patients with NB developed periorbital metastasis over an 18-month period. In the present study, we collected the clinical data of patients with periorbital metastasis of NB admitted to the Hematology-Oncology Center of Beijing Children's Hospital affiliated to Capital Medical University from March 2007 to March 2018.…”
Section: Introductionmentioning
confidence: 99%
“…Exophthalmos is also a typical symptom for metastatic foci located in the orbit. In children the most common metastatic tumor is neuroblastoma, originally located in the adrenal, retroperitoneal or mediastinal space [14]. The most prevalent malignant tumor affecting this region in children is rhabdomyosarcoma (RMS) [15].…”
Section: Discussionmentioning
confidence: 99%